Product Innovation, Lifestyle,Brand Reputation on Purchase Decision and Its Implications to Consumer Satisfaction - Juanim Juanim; Feiko Revoliady; Muhammad Iqbal Baihaqi (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2023)
The purpose of this study is to know the phenomenon and get empirical evidence, and alsoconclusion about the influence of the impact of product innovation, lifestyle and brandreputation on purchase decision and its implications to consumer satisfaction. This researchusing descriptive and verification methods. The sampling technique is sampling incidental.The research surveyed 140 respondents. Data analysis method of this research using. par pathanalysis. The result of this reveals that, product innovation, lifestyle, brand reputation, purchase decision and consumer satisfaction in the high category, and The impact of product innovation, lifestyle and brand reputation on purchase decision and its implications to consumer satisfaction by 67,7%.